Generating Cycles Reflected in a Century of Prices - Moore, Henry Ludwell (Quarterly Journal of Economics, 1921)
Cycles of approximately eight years in the yield per acre of British crops have probably recurred in a continuous series during the last one hundred and sixty years. In consequence of the law of demand, these crop cycles have generated corresponding cycles in the prices of food and of organic raw materials. In conformity with the law of competitive price, the cycles in the prices of food and of raw materials should have been followed by corresponding cycles in the prices of manufactured commodities. As a matter of fact, the analysis of Sauerbeck's index numbers of general wholesale reveals real cycles of approximately eight years in which the originating, generating crop cycles are reflected throughout the century for which the Sauerbeck index numbers have been computed. The principal results of the investigation appear in the graphs of Figures 5 and 6. I. Data and method, 504. — II. An analysis of a century of prices, 508. — III. Crop cycles as generating cycles, 515.